Modeling of bilevel games and incentives for sustainable critical infrastructure system - Miao, Xin; Yu, Bo; Xi, Bao; Tang, Yan-hong (Technological and Economic Development of Economy, 2010)
Implementation of sustainable development policy is a complex task and challenge for critical infrastructure management. Players in different levels related to critical infrastructure management try to maximize their own utilities and this process often leads to conflicts due to lack of cooperation, that is, noncooperative games exist in the management process of critical infrastructures. Noncooperative games may evolve to equilibrium state after long‐term numerous games and society and individuals have to pay enormous cost to this process. This paper focuses on the games and incentive mechanism in critical infrastructure management. The complicated game relation is analyzed and the bilevel game model is put forward. Game analysis helps us to understand the hidden interests and contradictions behind game problems so as to contribute to basic theory for policy making on sustainable critical infrastructure system. Through scientific design of incentive mechanism, the uncertainty of games can be reduced and the theoretical win‐win incentive compatibility models are put forward to improve the sustainability of critical infrastructure system. These models allow us to choose a more efficient way for the development and protection of critical infrastructures.Article in English.Lošimų teorijos taikymas modeliuojant būtinąją darnaus vystymosi infrastruktūrąSantrauka. Darnaus vystymosi politikos diegimas ir būtinosios infrastruktūros valdymas – sudėtingas uždavinys. Įvairios suinteresuotos grupės, susijusios su būtinosios infrastruktūros valdymu, siekia maksimizuoti savo naudą, o tai dažnai sukelia konfliktų. Konfliktų sprendimas trunka ilga laiką, todėl visuomenė ir pavieniai asmenys patiria daug nuostolių. Šiame straipsnyje sprendžiamos būtinosios infrastruktūros valdymo problemos, tam pasiūlytas lošimu teorijos modelis. Jis padeda atskleisti pasleptus interesus ir prieštaravimus, formuoti būtinosios infrastruktūros valdymo politika. Taikant mokslinius metodus sumažintas neapibrežtumas, sukurti teoriniai visas suinteresuotas puses tenkinantys būtinosios infrastruktūros modeliai, leidžiantys efektyviau kurti ir tausoti būtinaja infrastruktūrą.Reikšminiai žodžiai: lošimu teorija, lošimų teorijos raida, darnus vystymąsis, būtinoji infrastruktūra, matematinis modelis.First published online: 10 Feb 2011